Sistem Informasi Data Perkara Tindak Pidana Khusus Pada Kejaksaan Tinggi Aceh - Fikri, Muntazul; Imilda; Syarifuddin (Computer Journal, 2023)
The Aceh High Prosecutor's Office is one of the most important parts of the Unitary State of the Republic of Indonesia's High Prosecutor's office. The Aceh High Prosecutor's Office is the "spearhead" of the Prosecutor's Office, even the performance of the Aceh High Prosecutor's Office is often measured by the community through the success of the Aceh High Prosecutor's Office in handling specific criminal cases. One of the duties of the Aceh High Prosecutor's Office is to process data on case files which are numerous and complex. Good data management is needed to ensure that these data can be used to generate information and make decisions. From the description of the background, the author limits the problem only to the design of a special crime case data system at the Aceh High Prosecutor's Office. The purpose of the discussion is to find out and design a data system design for special criminal cases at the web-based Aceh High Court. For the perfection of this research, the authors collected data using several data collection methods, including using field studies and literature studies as well as the waterfall method as a system development model. The system will really help users or managers of special criminal case data at the Aceh High Court more quickly, easily and accurately in every activity related to Special Crimes.